REVENUE ANALYSIS OF POLE AND LINE FISHING IN SOUTHEAST MINAHASA REGENCY - Munirah Tuli; Alfi Sahri R. Baruadi; Funco Tanipu; Muhamad Thoriq Idris (Universitas Mataram, 2024)
Belang is a sub-district in Southeast Minahasa Regency, North Sulawesi, Indonesia. Most residents work as fishermen because the area is located on the southern coast. Skipjack (Katsuwonus pelamis) is a leading economic activity in the North Sulawesi fisheries sector, which is usually caught with pole and line (huhate) fishing gear. This study aims to assess the income of skipjack fisheries using the pole and line method in Belang Harbour, Southeast Minahasa Regency. The research was conducted from October to December 2023. The research method is by conducting interviews and observing the income of pole and line fisheries and analysed using Microsoft Excel. The results showed that the profit sharing system applied in each business unit at Belang Harbour was in accordance with the collective agreement. Sales revenue is reduced by total costs, then divided into 50% for the owner and 50% for the crew. The crew's share of 50% will be divided again according to their role/position on the ship. The skipper receives 30%, the KKM receives 20%, the boy-boy receives 20%, and the angler receives 30%. Variable and fixed costs for each pole and line business unit varied. The average variable cost for the five pole and line businesses in Belang Harbour was IDR 346,470,000, while the average fixed cost was IDR 48,315,000. The average revenue of the pole and line business at Belang Harbour for three months reached Rp 703,500,000, while the average income was Rp 307,815,000.